Glutathione Metabolism Is a Regulator of the Acute Inflammatory Response of Monocytes to (1→3)-β-D-Glucan - Ramendra, Rayoun; Mancini, Mathieu; Ayala, Jose-Mauricio; Tung, Lin Tze; Isnard, Stephane; Lin, John; Routy, Jean-Pierre; Nijnik, Anastasia; Langlais, David (Frontiers in Immunology, 2021)
(1→3)-ꞵ-D-Glucan (BDG) represents a potent pathogen-associated molecular pattern (PAMP) in triggering the host response to fungal and some bacterial infections. Monocytes play a key role in recognizing BDG and governing the acute host response to infections. However, the mechanisms regulating monocyte’s acute response to BDG are poorly understood. We sought to investigate the response of monocytes to BDG at the epigenetic, transcriptomic, and molecular levels. Response of human monocytes to 1, 4, and 24 hours of BDG exposure was investigated using RNA-seq, ATAC-seq, H3K27ac and H3K4me1 ChIP-seq. We show that pathways including glutathione metabolism, pentose phosphate pathway, and citric acid cycle were upregulated at the epigenetic and transcriptomic levels in response to BDG exposure. Strikingly, unlike bacterial lipopolysaccharides, BDG induced intracellular glutathione synthesis. BDG exposure also induced NADP synthesis, increased NADPH/NADP ratio, and increased expression of genes involved in the pentose phosphate pathway in a GSH-dependent manner. By inhibiting GSH synthesis with L-buthionine sulfoximine (BSO) before BDG exposure we show that the GSH pathway promotes cell survival and regulates monocyte’s effector functions including NO production, phagocytosis, and cytokine production. In summary, our work demonstrates that BDG induces glutathione synthesis and metabolism in monocytes, which is a major promoter of the acute functional response of monocytes to infections.